2015
DOI: 10.1007/s10554-015-0718-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the reliability of E/E′ to estimate pulmonary capillary wedge pressure in heart failure patients with preserved ejection fraction versus those with reduced ejection fraction

Abstract: Accurate assessment of pulmonary capillary wedge pressure (PCWP) is essential for physicians to effectively manage patients with acute decompensated heart failure. The ratio of early transmittal velocity to tissue Doppler mitral annular early diastolic velocity (E/E') is used to estimate PCWP noninvasively in a wide range of cardiac patients. However, it remains contentious as to whether mitral E/E' is a reliable predictor of PCWP. In the present study, acute heart failure patients were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Consistent with prior studies, our study confirmed that acute HFpEF predominantly affects old hypertensive women who present with acute dyspnoea and hypoxaemia. We further showed, using imaging and circulating biomarkers, that acute HFpEF and acute HFrEF shared similar features: (i) increased natriuretic peptides, (ii) increased pulmonary pressure, (iii) altered RV function, (iv) enlarged IVC, (v) altered renal function, and (vi) poor outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with prior studies, our study confirmed that acute HFpEF predominantly affects old hypertensive women who present with acute dyspnoea and hypoxaemia. We further showed, using imaging and circulating biomarkers, that acute HFpEF and acute HFrEF shared similar features: (i) increased natriuretic peptides, (ii) increased pulmonary pressure, (iii) altered RV function, (iv) enlarged IVC, (v) altered renal function, and (vi) poor outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies excluded patients in atrial fibrillation. Five studies used PCWP and four studies used LVEDP as reference parameter. Invasive measurements were simultaneous or directly after echo in seven out of nine studies.…”
Section: Resultsmentioning
confidence: 95%
“…Nine studies with invasive haemodynamic measurements are listed in Table . Most of these studies included a low number of patients ( n = 10–20), with only three studies having more than 40 HFpEF patients included.…”
Section: Resultsmentioning
confidence: 99%
“…In the HFrEF group, a cutoff of ≥30 B-lines showed a comparable sensitivity of 86% and a specificity of 78% (AUC: 0.84, 95% CI: 0.811-0.866) ( Figure 3). 16 Matsushita et al 17 reported that E/eʹ was positively correlated with pulmonary capillary wedge pressure (r=0.56, P=.01) in the HF with preserved ejection fraction group.…”
Section: Roc Of B-linesmentioning
confidence: 97%